Marketing department strategy to increase the amount of events in aruss semarang hotel: Marketing Department - Halim, Veronica; Rahayu, Emik (Journal of Gastro Tourism, 2024)
A large amount of hotels in Semarang city causing competitive environtment among them. Aruss Semarang Hotel was one of the hotels in Semarang City that located on Jl. Dr. Wahidin No. 116, Jatingaleh, Candisari. The sales marketing department on this hotel has implemented various marketing strategies to compete with it's competitors. However, with many marketing strategies that have been implemented, they still have several problems on increasing the amount of events. The problems coming from operational activity on human resources that caused by miscommunication. This research was using qualitative descriptive methods, with data collection techniques through observation, interview, and documentation. This research aims to analyze the obstacles that faced by the sales marketing department in carrying out the operational activity, giving the solutions, and suggestion of strategies that can be used to improving the events in Aruss Semarang Hotel. The strategies are 4P (Product, Place, Price, Promotion), 5 element of marketing promotion mix (Advertising, Public Relation, Sales Promotion, Direct Selling, and Personal Selling), application of CMR (Customer Relationship Management), marketing through Instagram celebrities and designing work programs to maximize MICE (Meeting, Incentive, Convention, and Exhibition). The results of this research has proven successfully proving to increase the event management on 2022-2023 by 55,6%.